The Journey of India’s Homeopathic Pharmaceutical Industry (Homoeopathy for All, 2024)
The Indian homeopathic pharma ceutical industry has undergone a  remarkable transformation from its  humble beginnings to becoming a  well-established ecosystem today.  Introduced in the early 19th century,  homeopathy initially flourished in  Bengal before spreading across In dia. Over time, the industry has wit nessed significant growth, with the  market for homeopathic products  projected to expand annually by 20- 25% and reach a substantial size of  INR 20-30 billion. Despite the small  market for homeopathic products  other than drugs in India, the sec tor has shown resilience and steady  progress.
Keywords: Pharmaceutical; Industry